INTELEKT PILLS VARIETIES USING ARTIFICIAL SELECTION AND ITS ROLE IN (Web of Technology: Multidimensional Research Journal, 2024)
This article is dedicated to the selection and varieties of pills effective detection using artificial intelligence. Artificial intelligence technologies, especially in image processing and pattern recognition algorithm has created new opportunities for assessing the quality of get the pills. Traditional methods based on the human eye, will spend time and into the error varies with predisposition to this industry in product quality negative effects to showwork, can. This research artificial intelligence from taking advantage, high-precision fast pills of varieties and the possibility of effective detection are studied. This article is based on analysis using artificial neuron networks of pills in the selection of images and shows them achieved. The production of the pills results confirms the importance of increasing productivity and quality in the field of artificial intelligence.